Importance of the stomach in maintaining calcium homoeostasis in the rat. Issue 11 (November 1991) - Axelson, J; Persson, P; Gagnemo-Persson, R; Håkanson, R
Abstract : The stomach helps to maintain calcium homoeostasis by making dietary calcium accessible for uptake in the intestines, although the effect of the stomach on calcium homoeostasis is poorly understood. We examined the effect on blood calcium of gastric surgery in the rat. Within three weeks gastrectomy and fundectomy (excision of the acid producing part of the stomach) induced a slight lowering of the blood calcium concentration. When parathyroidectomy was combined with either gastrectomy or fundectomy the blood calcium concentrations promptly dropped to values lower than after parathyroidectomy alone. The mortality was close to 100% during the first three weeks after combined parathyroidectomy and gastric surgery. It was nil in rats subjected to parathyroidectomy alone. Gastrectomised rats absorbed Ca2+ better than unoperated control rats, possibly reflecting the fact that the serum 1, 25-dihydroxyvitamin D concentration was raised. Gastrectomised rats had a food intake that was about 70% of that in intact rats, and the amount of dietary calcium absorbed (net absorption per kg body weight) by the gastrectomised rats was approximately 65% of that in intact control rats. We conclude that the acid producing part of the stomach is important for calcium homoeostasis, since its removal induced lethal hypocalcaemia in parathyroidectomised rats. One possible explanation for the hypocalcaemia induced by gastrectomy is a progressive calcium deficit. In addition, the loss of calciotrophic hormones originating in the stomach may contribute.